2017
DOI: 10.18632/oncotarget.20503
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq reveals distinctive RNA profiles of small extracellular vesicles from different human liver cancer cell lines

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 78 publications
4
30
1
Order By: Relevance
“…IsomiRs with variations at the 3′ end were the predominant isomiR category identified in our data in both stem cell types (Fig. 8 ), and the ratio of isomiR reads to canonical miRNA reads was similar to earlier studies 33 , 73 . Exact function of isomiRs with 3′ modifications are not clearly known but are suggested to be related to a disease state 74 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IsomiRs with variations at the 3′ end were the predominant isomiR category identified in our data in both stem cell types (Fig. 8 ), and the ratio of isomiR reads to canonical miRNA reads was similar to earlier studies 33 , 73 . Exact function of isomiRs with 3′ modifications are not clearly known but are suggested to be related to a disease state 74 .…”
Section: Discussionsupporting
confidence: 90%
“…A low percentage of miRNA reads is typical to extracellular vesicle samples 8 , 28 33 . Although the number of miRNA reads per sample was relatively low, miRNA reads were of high quality and mostly close to full length (Supplemental 5), as well as showed robust expression in both sample types (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were isolated from rBMSCs and from EVs derived from the same rBMSCs using M-PER Mammalian protein extraction reagent supplemented with 1% of Halt Protease, EDTA-free phosphatase-inhibitor cocktail and 1% of EDTA solution (all from Thermo Fisher Scientific), according to the manufacturer's indications [6]. Protein extracts were stored at -20˚C.…”
Section: Protein Preparation From Cells and Evsmentioning
confidence: 99%
“…Recent investigations suggest that the therapeutic efficacy of MSCs depends on paracrine mechanisms and, more recently, their therapeutic potential has been attributed to the secretion of extracellular vesicles (EVs), which are membrane-enclosed lipid vesicles released by cells as mediators of intercellular communication. Ranging in size from *50 nm to > 1μm, EVs carry functional proteins, DNA, mRNA, ncRNA and lipids [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Gene profiling and protein expression analysis of EVs isolated from metastatic HCC cells identified the mesenchymal-epithelial transition (MET) proto-oncogene S100 family members and caveolins as tumor-promoting molecules in HCC [42,43]. Considerable evidence has indicated that miRNAs contained in EVs contribute to metastasis, chemoresistance, and immunomodulation in different cancer types, including HCC [44]. Min Shi and co-authors have studied the diagnostic and prognostic use of serum EV-miR-638 in HCC patients.…”
Section: Extracellular Vesicles In Hepatocellular Carcinomamentioning
confidence: 99%